Writing material culture history - Gerritsen, Anne; Riello, Giorgio (Writing history, 2015)
"This new edition of Writing Material Culture History examines the methodologies currently used in the historical study of material culture. Touching on archaeology, anthropology, art history and literary studies, the book provides history students with a fundamental understanding of the relationship between artefacts and historical narratives. The role of museums, the impact of the digital age and the representations of objects in public history are just some of the issues addressed in a book that brings together distinguished scholars from around the world"--